Sarah's incredible idea - O'Connor, Jane.; Long, Laurie Struck (New York : Grosset & Dunlap, 1993)
Shy Sarah has a great idea for her Brownie Girl Scout troop but is not sure she is brave enough to speak up.
Booklist.
Horn Book.
3.5
K-3
Keywords: Courage -- Fiction; Girl Scouts -- Fiction; Courage -- Fiction; Girl Scouts -- Fiction